HBR's 10 Must Reads on Sales - Review, Harvard; Kotler, Philip; Zoltners, Andris; Goyal, Manish; Anderson, James (Ascent Audio, 2020)
Sales isn't about pushing products or being efficient; it's about building the right systems to manage and empower your salespeople. We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you understand how to create the conditions for sales success. This book will inspire you to: understand your customer's buying center, integrate your sales and marketing operations, assess your business cycle and its impact on your sales force, transition away from solution sales, leverage the power of micromarkets, introduce tiebreaker selling and consensus selling, and motivate your sales force properly.